2021
DOI: 10.2298/pan150428004c
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of wheat prices using multiple structural breakpoint co-integration test

Abstract: From 2005 to 2008, high volatility in the markets affected grain prices significantly. This high volatility in grain prices made many researchers curious, and many discussions aroused from this topic. This study analyzes wheat price behavior during this period of high volatility. We estimate a return index for wheat using spot and futures wheat prices with the help of a present value model. To analyze the cointegration between the wheat prices and return index, a new co-integration test with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Jian Yang and David J. Leatham analysed the U.S. wheat futures market and found that in the long run, wheat futures market prices are relatively balanced and there is no price convergence in the wheat futures markets of different countries [6]. Cinar, Gokhan's study shows that there is a cointegration relationship between spot and futures prices of wheat, in other words, there is an equilibrium relationship between them [7]. When it refers to the Australian futures market, Turkington, J & Walsh, D study tells us that electronic markets have enhanced price discovery in the current environment, but price discovery is still very slow.…”
Section: Introductionmentioning
confidence: 99%
“…Jian Yang and David J. Leatham analysed the U.S. wheat futures market and found that in the long run, wheat futures market prices are relatively balanced and there is no price convergence in the wheat futures markets of different countries [6]. Cinar, Gokhan's study shows that there is a cointegration relationship between spot and futures prices of wheat, in other words, there is an equilibrium relationship between them [7]. When it refers to the Australian futures market, Turkington, J & Walsh, D study tells us that electronic markets have enhanced price discovery in the current environment, but price discovery is still very slow.…”
Section: Introductionmentioning
confidence: 99%